2017
DOI: 10.1128/aac.01024-17
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Sensitizes Anoxic Pseudomonas aeruginosa Biofilm to Ciprofloxacin

Abstract: Chronic Pseudomonas aeruginosa lung infection is characterized by the presence of endobronchial antibiotic-tolerant biofilm, which is subject to strong oxygen (O2) depletion due to the activity of surrounding polymorphonuclear leukocytes. The exact mechanisms affecting the antibiotic susceptibility of biofilms remain unclear, but accumulating evidence suggests that the efficacy of several bactericidal antibiotics is enhanced by stimulation of aerobic respiration of pathogens, while lack of O2 increases their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 49 publications
(64 reference statements)
4
53
0
Order By: Relevance
“…In the experimental condition, the bacteria were allowed 20 h of growth to establish a biofilm before GEN administration. Plate counts revealed that over this period bacterial counts in the inoculated bead rose from the initial inoculum concentration of ~log 10 5.4 colony-forming units per milliliter to about log 10 9.2 colony-forming units per milliliter ( Figure 5), while beads adjacent to the inoculated bead experienced a growth from 0 to log 10 4.4 colony-forming units per milliliter (P < .001 and P = .015, respectively). After this point, in contrast to the rapid depletion of oxygen in the absence of antibiotic, the onset of GEN exposure coincided with a "freezing" of the oxygen sink, characterized by ongoing oxygen usage but a complete lack of sink spatial expansion.…”
Section: F I G U R E 1 Calibration Curve Relating the Response Of Spimentioning
confidence: 96%
“…In the experimental condition, the bacteria were allowed 20 h of growth to establish a biofilm before GEN administration. Plate counts revealed that over this period bacterial counts in the inoculated bead rose from the initial inoculum concentration of ~log 10 5.4 colony-forming units per milliliter to about log 10 9.2 colony-forming units per milliliter ( Figure 5), while beads adjacent to the inoculated bead experienced a growth from 0 to log 10 4.4 colony-forming units per milliliter (P < .001 and P = .015, respectively). After this point, in contrast to the rapid depletion of oxygen in the absence of antibiotic, the onset of GEN exposure coincided with a "freezing" of the oxygen sink, characterized by ongoing oxygen usage but a complete lack of sink spatial expansion.…”
Section: F I G U R E 1 Calibration Curve Relating the Response Of Spimentioning
confidence: 96%
“…Another promising approach is to supply extra O 2 to hypoxic environments [ 41 , 107 , 108 ] to overcome the antibiotic tolerance in established biofilms where dormant bacteria are present. Hyperbaric O 2 treatment (HBOT) has previously been used as an adjuvant to ciprofloxacin on P. aeruginosa [ 109 , 110 ], but the underlying mechanism still needs to be investigated thoroughly.…”
Section: Treatments To Tackle the Broad Spectrum Of Growth Ratementioning
confidence: 99%
“…Increased antimicrobial tolerance, a fundamental property of biofilms [12] is well-studied [13] and four mechanisms play a major role: (i) under nutrient-limited conditions in biofilms, P. aeruginosa expresses phenotypic variants, i.e., dormant cells that are less susceptible to antibiotics which target actively dividing cells [14]; (ii) P. aeruginosa form a protective extracellular matrix composed of polysaccharides, proteins and DNA that limits the diffusion of antimicrobial substances or sequesters them, such that biofilm cells experience a decreased antimicrobial dosage [15]; (iii) anoxic conditions exist within the biofilm limiting the efficacy of antibiotics that require aerobic metabolic activity and the generation of reactive oxygen species [16]; (iv) sub-inhibitory concentrations of antibiotics induce increased rates of mutation, recombination and lateral transfer. The mutation rate in biofilms has been reported to be up to 100 times higher than in planktonic cells [17], significantly accelerating the development of antibiotic resistant mutants.…”
Section: Staphylococcus Aureus Klebsiella Pneumoniae Acinetobactermentioning
confidence: 99%